Endothelin‐1 levels are decreased in pediatric Type 1 diabetes and negatively correlate with the carotid intima media thickness. Issue 6 (3rd June 2021) - Cohen, Michal; Yaseen, Hiba; Khamaisi, Mogher; Gendelman, Raya; Zuckerman‐Levin, Nehama; Shilo, Smadar; Ilivitzki, Anat; Weiss, Ram; Shehadeh, Naim
Abstract: Aims: Better understanding of the timeline and risk factors for the appearance of complications in pediatric Type‐1‐diabetes is key for developing prevention strategies. We studied endothelial markers and their determinants in adolescents with Type‐1‐diabetes at different time points from diagnosis. Methods: A cross‐sectional study of 58 adolescents, mean age 15.0 ± 2.4 years; 20 with recent‐onset Type‐1‐diabetes, 20 with over 7 years of Type‐1‐diabetes and 18 controls. Clinical and biochemical data were collected. Fingertip arterial reactive hyperemia (EndoPAT) and carotid intima‐media‐thickness (cIMT) were measured to assess endothelial function and structure. Results: Compared to controls, individuals with prolonged Type‐1‐diabetes had higher mean cIMT (0.49 ± 0.07 mm vs. 0.43 ± 0.05 mm p  = 0.021) and maximal cIMT (0.61 ± 0.08 mm 0.52 ± 0.08 mm, p  = 0.025). Endothelin‐1 levels were significantly lower in subjects with prolonged Type‐1‐diabetes (1.2 ± 1.0 pg/ml) compared to controls (3.0 ± 1.7, p  = 0.008 pg/ml); they negatively correlated with the mean cIMT ( c  = − 0.291, p  = 0.031) and mean 6 months hemoglobin A1c ( c  = − 0.301, p  = 0.022) and positively correlated with mean c‐peptide levels ( c  = 0.356, p  = 0.006) and the weekly exercise time ( c  = 0.485, p  < 0.001). Endothelin‐1 levels did not correlate with EndoPAT results. Conclusions: Our results suggest that the early years after the diagnosis of Type‐1‐diabetes are an important window for prevention of arterial damage in the pediatric population. The trajectories of relationships of Endothelin‐1 with metabolic and vascular measures were opposite from the anticipated, yet consistent. Endothelin‐1 related indirectly to adverse measures and directly to favorable measures. Decreased Endothelin‐1 levels might reflect early stages in endothelial impairment in Type‐1‐diabetes, yet its' exact role in the development of complications is yet to be unraveled.